2009
DOI: 10.1111/j.1442-2042.2009.02252.x
|View full text |Cite
|
Sign up to set email alerts
|

Lower urinary tract symptoms and their impact on quality of life after successful renal transplantation

Abstract: Objective: To investigate lower urinary tract symptoms (LUTS) and their impact on quality of life (QOL) in patients having undergone renal transplantation (RTX). Methods: Forty-three patients (25 males and 18 females; age 20-68 years) undergoing RTX at Hokkaido University Hospital were included in this study. Median follow-up after RTX was 41 months (range 6-184). Pre-transplant dialysis had been carried out in 38 patients (median: 4.3 years, range: 1 month-31 years). All patients were assessed by uroflowmetry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…A previous study reported that LUT dysfunction and LUT symptoms did not significantly affect the QOL of patients who underwent RTX [19], except for nocturia and nocturnal polyuria [9]. However, these findings are controversial because patients who underwent RTX do not need renal replacement therapy and may perceive changes in LUT symptoms as positive.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…A previous study reported that LUT dysfunction and LUT symptoms did not significantly affect the QOL of patients who underwent RTX [19], except for nocturia and nocturnal polyuria [9]. However, these findings are controversial because patients who underwent RTX do not need renal replacement therapy and may perceive changes in LUT symptoms as positive.…”
Section: Discussionmentioning
confidence: 91%
“…Dion et al reported that low urine output before RTX was predictive of LUT symptoms, which were not uncommon after RTX [20]. Voiding dysfunction has also been frequently observed in patients who underwent RTX [7][8][9]. Thus, screening for LUT symptoms and LUT dysfunction is important, even in patients who successfully underwent RTX, because they may induce urinary tract infections and vesicoureteral reflux and their related complications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be known that it is very difficult to predict incidence of BPH because of dialysis-dependent oliguric or anuric life span. [11] When the outcomes of end-stage renal failure patients who had undergone TURP with the diagnosis of BPH before transplantation were evaluated, oliguric, and anuric state of these patients were observed to be a high risk for the postoperative development of bladder neck stricture. [12] Therefore, it has been suggested that surgeries should be deferred after transplantation in patients diagnosed as BPH irrespective of their oliguric or anuric state before transplantation because of higher incidence of postoperative morbidity.…”
Section: Discussionmentioning
confidence: 99%